Isolated cystic cervical oesophageal duplication: a rare congenital anomaly. (14th November 2012) - Verma, Shraddha; Garge, Saurabh; Samujh, Ram; Narasimha, Rao Katragadda Lakshmi
Abstract : Oesophageal duplication is a rare congenital anomaly. The cystic form is the usual presentation of the duplication, found predominantly in the lower third. Less than 20 cases of isolated cystic oesophageal duplication in the cervical region have been reported till date in the English literature. We are reporting this case because of its rarity.